Sofosbuvir-based therapies associated with regression of liver fibrosis in patients with hepatitis C virus infection: A prospective observational study. Issue 12 (26th March 2021) - Nozaki, Akito; Chuma, Makoto; Hara, Koji; Moriya, Satoshi; Fukuda, Hiroyuki; Numata, Kazushi; Tanaka, Katsuaki; Morimoto, Manabu; Sakamaki, Kentaro; Yamanaka, Takeharu; Kondo, Masaaki; Maeda, Shin
Abstract : Abstract: Oral direct-acting antiviral (DAA) treatment leads to >95% sustained virological response (SVR) and could be clinically useful in regression of liver fibrosis in chronic hepatitis C virus (HCV) infection. We evaluated if ledipasvir/sofosbuvir or sofosbuvir + ribavirin is associated with regression of fibrosis in HCV patients who achieved SVR. In this prospective cohort study performed at 3 sites in Japan, patients with genotype 1 and genotype 2 were given standard treatment of ledipasvir 90 mg/sofosbuvir 400 mg and sofosbuvir 400 mg + 200–1000 mg/day ribavirin, respectively, for 12 weeks. Liver fibrosis was assessed using Mac-2-binding protein glycosylation isomer (M2BPGi) and other fibrosis markers (platelet count, Fib-4 index, liver stiffness measurement [LSM]) in patients who achieved SVR. A total of 98.1% of (n = 101/103) patients in genotype 1 cohort and 100% (n = 16/16) in the genotype 2 cohort achieved SVR12. Based on per-protocol analysis, M2BPGi levels showed a significant decrease (–2.2 cut-off index [COI], P < .0001) at week 48 after treatment initiation. Forty-three patients showed a significant decrease in Fib-4 index (–1.2, P < .0001), and 44 patients showed improvement in LSM (–5.9 kPa, P < .0001). Achievement of SVR after antiviral therapy was associated with fibrosis regression. M2BPGi correlated well with LSM at week 48 after treatment initiation, supporting the sustainable benefit of HCV therapy.